Karl Barth og erfaringens plass i teologien = The Place of Experience in the Theology of Karl Barth - Rasmussen, Filip (2024)
Det sies ofte, særlig i en norsk kontekst, at Karl Barth ikke fant noen plass for erfaringen i teologien. Denne artikkelen argumenterer derimot for at Barth ikke er kritisk til erfaring som sådan, men bare til "umiddelbar erfaring", det vil si en form for erfaring som går forut for og ikke fullstendig kan formidles gjennom språk og refleksjon. Artikkelen argumenterer videre for at Barth ikke har noen problemer med to vanlige forståelser av erfaringens plass i teologien: Han har ingen problemer med at dogmatikken må ta hensyn til menneskelig kunnskap som sådan og menneskets egen samvittighet, og han mener at det nettopp er i den praktiske anvendelsen av dogmatikken i vår erfarte verden at dogmatikken finner sin berettigelse.
It is often said, especially in a Norwegian context, that Karl Barth rejected the place of experience in theology. This article argues that Barth is not in any way critical towards experience as such, but rather only towards "immediate experience", i.e., a form of experience that precedes and cannot be fully articulated through language and reflection. The article furthermore argues that Barth does not have any problem with two common nuances of "experience": He has no problem with the claim that the work of dogmatics must heed and engage human knowledge as such and the conscience of the human being, and he believes that it is in the practical application of dogmatics in our world of experience that the work of dogmatics is justified.
Keywords: Karl Barth; erfaring; Experience; history of theology; Revelation; teologihistorie; åpenbaring